The Pentecostal Gospel of Prosperity in African Contexts of Poverty: An Appraisal - Togarasei, Lovemore (Exchange, 2011)
Abstract This paper discusses the paradox presented by two realities: the situation of extreme poverty in sub-Saharan Africa and the rapid growth of charismatic Pentecostal Christianity with its emphasis on prosperity. Earlier studies on Pentecostalism have identified its success among the poor as a result of its promise of prosperity. Indeed others have viewed this doctrine as an impetus for delusion. This paper critically reviews the Pentecostal gospel of prosperity in the context of the poverty experienced in sub-Saharan Africa. In particular, it discusses the possible contribution of this doctrine to sustainable development. Over and above a theorization of how this gospel can contribute to sustainable development for poverty reduction, the paper also discusses specific cases of how Pentecostal Christianity is contributing to poverty reduction in Zimbabwe and Botswana, for example.
paid
Keywords: African Christianity; Pentecostalism; Poverty; Prosperity Gospel; Southern Africa